STRATEGI DIGITAL MARKETING UMKM DALAM AKUNTANSI PEMBIAYAAN - Aulia Parsa Nadhiraah; Rima Ayu Khornellia; Annisa Ragellea Andiani; Muhammad Djasuli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in driving economic development in Indonesia. However, there are some major challenges that often occur is the difficulty of getting access to proper financing. This research aims to explore the application of digital marketing strategies by MSMEs in order to increase transparency and accountability related to business financing. The research was conducted through a literature review to understand the contribution of digital technology in supporting small business sustainability. The findings show that the use of social media, online sales platforms (e-commerce), and digital financial recording applications can help MSMEs expand their market reach and generate more organized financial data. Not only does this have an impact on increasing turnover, but it also makes it easier for MSMEs to gain trust from financial institutions thanks to clearer and more systematic financial reports. Therefore, this study suggests that MSMEs combine digital marketing strategies with a good financial management system to improve competitiveness in a sustainable manner.